Neurolinguistic Profiles of Language Impairment and Recovery in Indonesian-Speaking Post-Stroke Aphasia Patients - Tammasse; Jumraini; Muhayyang, Maemuna; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
Post-stroke aphasia is a complex language disorder resulting from damage to brain regions responsible for linguistic function. This study aims to identify patterns of language impairment and potential recovery in aphasic patients using a neurolinguistic approach based on Bahasa Indonesia. Employing a qualitative descriptive design, data were collected from ten outpatient aphasia patients at RSUP Dr. Wahidin Sudirohusodo, Makassar, through structured linguistic interviews, adapted language assessment tools (BNT-Ina and MoCA-Ina), and transcription of spontaneous speech. The findings reveal varied disruptions across five linguistic components—phonology, morphology, syntax, semantics, and pragmatics—depending on the type of aphasia. Broca’s aphasia is characterized by agrammatism and articulatory deficits with preserved comprehension; Wernicke’s aphasia features fluent but semantically incoherent speech and poor understanding; while Global aphasia involves extensive impairment across all language domains. The analysis demonstrates how the agglutinative morphology and flexible syntax of Bahasa Indonesia influence the manifestation of aphasia and the design of rehabilitation strategies. Language recovery is interpreted through the lens of neuroplasticity, showing compensatory activation in non-dominant brain areas and improved outcomes through culturally contextual, mother-tongue-based therapy. This study contributes to the development of linguistically informed, localized aphasia interventions and underscores the importance of integrating neurolinguistic and sociocultural factors in language rehabilitation.